Developing and Validating MCA-Equivalent Summative Assessment in Combinatorics Using Aiken’s V Method - Nabilah, Nurjihan; Sari, Sovy Dia Permata; Sari, Yurizka Melia (Edumatika, 2025)
This study aims to analyze the content validity of summative assessment items in Combinatorics that are aligned with the Minimum Competency Assessment (MCA) framework. The study was motivated by the need for valid and high-quality assessment tools that support meaningful and sustainable mathematics learning. This study employed a research and development (R&D) design but it focuses primarily on the Develop stage, which aims to obtain a valid summative assessment instrument. The Aiken’s V method was used to measure the content validity of nine multiple-choice items developed according to the MCA numeracy domains, cognitive levels, and contexts. Three mathematics education experts served as validators. The analysis showed that the Aiken’s V indices ranged from 0.64 to 0.73, indicating medium validity. These results suggest that the instrument can be used after minor revisions. The validated instrument provides a reference for educators to design MCA-oriented summative assessments that enhance students’ mathematical literacy and reasoning skills. Future research may apply other validation methods such as Gregory’s analysis to strengthen the evidence of validity.